Low-energy cooling and ventilation refurbishments for buildings in a Mediterranean climate. (4th July 2022) - Spentzou, E.; Cook, M. J.; Emmitt, S.
ABSTRACT: In view of the ageing domestic building stock and increasing reliance on fossil fuels for cooling and ventilation of buildings, there is an urgent need for improved design knowledge and sustainable measures such as natural ventilation and passive cooling to mitigate climate change and future proof the built environment. This paper forms an appraisal of a range of low-energy refurbishment measures, i.e. building design alterations and passive systems, which were employed and evaluated in an apartment building in Greece. The applicability of these in domestic buildings in hot climates is assessed and their design implications evaluated. Implementation of wind-catchers, dynamic façades, and evaporative cooling had the highest ventilation and cooling potential, while improvements of the interior layout to allow for new airflow paths could provide further cooling to spaces and solutions to safety.